Gold leaching process and recovery from gold scraps using ascorbic acid - Sharizan, Ibrahim (Universiti Malaysia Perlis, 2011)
A new process of gold leaching which involves the use of hydrochloric acid, sulphuric acid and sodium nitrate was studied. A series of screening study was conducted to identify the most suitable of these acids that capable of dissolving gold completely. This was achieved by altering the concentration of hydrochloric acid and sulphuric acid while the amount of sodium nitrate was remained constant. It is concluded that the optimal dissolving condition depends on the concentration of the acids which was between 1 M to 6 M and 6 M to 11.5 M for sulphuric acid and hydrochloric acid, respectively and the dissolution rate depends on temperature of the solution and it is found that the optimum temperature is between 90°C to 150°C. The reaction order is second order with respect to the concentration of hydrochloric acid and sodium nitrate respectively. The reaction order for the sulphuric acid concentration is zero order. From the temperature dependence of rate measurement, the values of activated energy, entalphy and entrophy are -4.6k.Jmor1, -3.90 kJ mol1 and -291 J mol"1 K"1, respectively. The amount of dissolved gold was determined gravimetrically and the recovery of gold was achieved by precipitation with ascorbic acid. The study showed that ascorbic acid is capable to recover gold up to 99.9%. Analysis by cupellation method found that the fineness of refined gold is 998 fine or 99.8% of purity. Finally a brief comparison of this dissolution system and aqua regia method was reviewed and it is concluded that this method is suitable for small and medium scale refining.